HUBUNGAN PENGETAHUAN DAN MOTIVASI DENGAN PERILAKU IBU HAMIL MENGGUNAKAN KOSMETIK PEMUTIH - Irfana Tri Wijayanti; Siti Marfu’ah (LPPM STIKES KENDAL, 2019)
Abstrac Based on a preliminary survey of 15 pregnant women, consisting of 8 (53.33%) pregnant women using cosmetics had good knowledge and wanted to look beautiful. While 7 (46.66%) pregnant women did not use whitening cosmetics 5 (71.4%) pregnant women had good knowledge and wanted to appear as they are. The purpose of this study was to determine the relationship between knowledge and motivation with the behavior of pregnant women using free whitening cosmetics on the market (Non-Bpom) in Baturejo Village, Pati Regency. The design of the study uses correlative analytics, with a crossectional approach. Sample in the study there were 34 pregnant women. The technique in research uses random sampling techniques. The statistical test used is chi square. The results of the study on 34 pregnant women found 18 (52.94%) pregnant women had enough knowledge. 16 (47.05%) Pregnant women have high motivation to use cosmetics. 19 people (55.88%) pregnant women behave using cosmetics. Bivariate results on knowledge variables showed X2 count> X2 (10,531> 3,841), p value (0,005 <0,05) which means there was a relationship between the knowledge of pregnant women and the behavior of pregnant women using non-Bpom market whitening cosmetics in Baturejo Village District Starch. While the motivation variable shows X2 count> X2 (7.889> 3.841), p value (0.005 <0.05) which means that there is a relationship between the motivation of pregnant women and the behavior of pregnant women using market-free whitening cosmetics (Non-Bpom) in Pati Baturejo Village. Suggestions for health workers to provide counseling to pregnant women about the effects of cosmetics and their contents which are harmful to the skin, mother and fetus Keywords: Knowledge, Motivation, Self-Esteem, Behavior of Pregnant Women Using Bleaching Cosmetics